КАТИОНИТ КУ-2-8 ИШТИРОКИДА 4-МЕТИЛ ФЕНОЛНИ α–ФЕНИЛЭТИЛСПИРТ БИЛАН АЛКИЛЛАШ (Scientific journal of the Fergana State University, 2023)
The article presents the results of the reaction of 4-methylphenol with α–phenylethyl alcohol in the presence of cation exchange resin KU-2-8. The possibility of alkylation of phenols in the presence of an environmentally safe catalyst with high yield.